Motivated Forgetting in Early Mathematics: A Proof-of-Concept Study - Ramirez, Gerardo (Frontiers in Psychology, 2017)
Educators assume that students are motivated to retain what they are taught. Yet, many students commonly report that they forget most of what they learn, especially in mathematics. In the current study , I ask whether students may be motivated to forget mathematics because of academic experienceswhether maintaining high math anxiety and math self-perceptions create a threat to the self which spurs a motivation to forget threaten the self-perceptions they are committed to maintainingacademic experiences. Using a large dataset of 1st and 2nd grade children (N=812), I hypothesize that math anxiety creates negative experiences in the classroom that threaten children’s positive math self-perceptions, which in turn spurs a motivation to forget mathematics. I argue that this motivation to forget is activated during the winter break, which in turn reduces the extent to which children grow in achievement across the school year. Children were assessed for math self-perceptions, math anxiety and math achievement in the fall before going into winter break. During the spring, children’s math achievement was measured once again. A math achievement growth score was devised from a regression model of fall math achievement predicting spring achievement. Results show that children with higher math self-perceptions indeed showed reduced growth in math achievement across the school year as a function of math anxiety. Children with lower math interest self-perceptions did not show this relationship. Results provide correlational evidence serve as a proof-of-concept for a scientific account of motivated forgetting within the context of education. I argue that this motivation to forget is activated during the winter break, which in turn reduces the extent to which children grow in achievement across the school year.